2021
DOI: 10.1093/ofid/ofab033
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Recommendation and Quality of Evidence for Recommendations in Current Infectious Diseases Society of America Guidelines

Abstract: Background Grading of Recommendations Assessment, Development, and Evaluation (GRADE) is a systematic approach to grading strength of recommendation (SOR) and quality of evidence (QOE) for guideline recommendations. We aimed to assess the relationship between SOR and QOE in current Infectious Diseases Society of America (IDSA) guidelines. Methods In this cross-sectional analysis, we analyzed the frequency of SOR-QOE pairings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Our findings mirror that of other studies which evaluated SRs in CPGs in gastroenterology, cardiology, and infectious disease 49–51 . In the field of otolaryngology, a study conducted by Heigle et.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings mirror that of other studies which evaluated SRs in CPGs in gastroenterology, cardiology, and infectious disease 49–51 . In the field of otolaryngology, a study conducted by Heigle et.…”
Section: Discussionsupporting
confidence: 89%
“…48 Our findings mirror that of other studies which evaluated SRs in CPGs in gastroenterology, cardiology, and infectious disease. [49][50][51] In the field of otolaryngology, a study conducted by Heigle et. al, found that 47.2% of SRs in regards to the treatment of Meniere's disease had an appraisal rating of critically low, and none of which that highly adhered to the AMSTAR-2 checklist.…”
Section: Discussionmentioning
confidence: 99%
“…The group constructed a charter that specifically chose not to use the GRADE system for evaluating strength of evidence based on previously published concerns regarding bias, poor interrater reliability, and, most importantly, the dissociation between strength of recommendation and quality of evidence (Supplement 1). [1][2][3][4][5][6][7] Instead, the group sought to incorporate the "humility of uncertainty" 7 by only providing clear recommendations when reproducible, high-quality, hypothesis-confirming evidence is available, requiring at a minimum: (1) 1 properly conducted, adequately powered randomized controlled trial (RCT); and (2) at least 1 other concordant, prospective, controlled clinical study-either a second RCT, a quasi-experimental pre-post study, a pragmatic nonrandomized trial, or a carefully conducted historically controlled study. In the absence of such data, the charter requires provision of clinical reviews that discuss care choices.…”
Section: Methodsmentioning
confidence: 99%
“…An initial assessment of studies on COVID showed that many of them were of low quality [ 5 ]. Poor quality of evidence usually, though not always, translates into lower strength of recommendations, which may have serious public health implications [ 6 ]. This creates problems for decision-makers, as they are unable to weigh the evidence or identify research that is relevant to them [ 7 ].…”
Section: Introductionmentioning
confidence: 99%